The Value of Dialect amongst Kāi Tahu: Kā puananī o Tahu Pōtiki, he Manawa Reo, he Manawa Kāi Tahu1. (September 2014) - White, Tāwini; Rewi, Poia
For 'linguists to have any impact on reversing diminishing linguistic diversity', says Muhlhauser (in Austin and Sallabank, 2011: 31), 'they must focus their efforts on preserving language ecologies, not languages'. This article focuses on the preservation of dialect by the Kāi Tahu, as experienced by attendees of their own language ecology, Kura Reo Kāi Tahu, what motivates them to attend, and the support mechanisms that afford attendance. It discusses the relationship between identity and language, including discussion on standardised languages and dialect. Through research findings, it then reports on the awareness of Kāi Tahu members towards their dialect after which it shares their views on the enablers and disablers of their use of the dialect. Finally, we see the respondents' views on the value of the Kāi Tahu dialect to them prior to introducing Zero—Passive—Active (ZePA), a model that provides an alternative approach to viewing language revitalisation.